(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-201-212 The problem of maintaining media diversity, as an important condition for the quality of the news sphere and for civic awareness, becomes relevant in the context of the algorithmicization of news and the dominance of "digital intermediaries". The latter are gaining discursive power, partially taking over the gatekeeping function from traditional journalism. Using the example of news aggregators as influential "secondary gatekeepers", the dynamics of quantitative and qualitative manifestations of media diversity they create are defined. Three common conceptualizations of media diversity serve as the theoretical basis. The author proceeds from the standard of open diversity. The evaluation of news diversity is made according to the parameters of variability, proportionality and balance. The dynamics of the following parameters were revealed: types of media (ownership, ideological position, national affiliation); the presence of a critical message; the nature of the sources used. The following trends were detected: a bias toward the dominance of state-owned media, an increase in the weight of state-owned news agencies, a decrease in the share of opposition publications, rejection of the practice of aggregating of foreign news media. The share of critical materials and "non-elite" sources of information has decreased. The results show the risks of news depletion in algorithmically curated environments, mainly under the influence of state media policy. Keywords: media diversity, news aggregator, digital intermediary, digital gatekeeping, digital media ecology, media politics, discursive control